Asset Recovery for Victims of “Binary Option” Case in Review of International Criminal Law - Ezzah Nariswari Lupianto (Faculty of Law, Universitas Lampung, 2022)
The Binary Options Trading Platform, also known as Binomo, is becoming increasingly popular due to the massive number of advertisements appearing on Youtube, affiliates who are influencers have caused many application users to disguise themselves as trading investments which then fall victim to it. Indra Kenz has been named a suspect in fraud and money laundering under the guise of Binomo investment. The flow of funds for this investment is indicated to a number of countries in the world, not only in Indonesia, so the Binomo case is included in the realm of international crime. In this case can the binomo victim's money be returned? In this study, the empirical juridical method is used, referring to written regulations/laws and then analyzing how it is implemented in the field. This study emphasizes the rules in legal science (legal aspects) and the practice carried out in the field. This study also discussed crime without criminal prosecution by using the NCB Asset Forfeiture concept. This research is descriptive, using primary legal materials and secondary legal materials. Data collection techniques with a literature study of legal materials are also carried out. The results of the study found that it is necessary to expand and add international legal regulations in implementing the return of assets resulting from transnational crimes so that assets resulting from crimes with indications of money laundering can be confiscated and returned to victims, as well as an effective mechanism for returning assets resulting from crimes, namely through civil lawsuits against assets.